Optimum Growth when Technology is Changing - Mirrlees, J. A. (Review of Economic Studies, 1967)
Journal Article Optimum Growth when Technology is Changing Get access J. A. Mirrlees J. A. Mirrlees Trinity College, Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 34, Issue 1, January 1967, Pages 95–124, https://doi.org/10.2307/2296573 Published: 01 January 1967